TATA-box DNA binding activity and subunit composition for RNA polymerase III transcription factor IIIB from Xenopus laevis. - McBryant, S J (1996)
The RNA polymerase III transcription initiation factor TFIIIB contains the TATA-box-binding protein (TBP) and polymerase III-specific TBP-associated factors (TAFs). Previous studies have shown that DNA oligonucleotides containing the consensus TATA-box sequence inhibit polymerase III transcription, implying that the DNA binding domain of TBP is exposed in TFIIIB. We have investigated the TATA-box DNA binding activity of Xenopus TFIIIB, using transcription inhibition assays and a gel mobility shift assay. Gel shift competition assays with mutant and nonspecific DNAs demonstrate the specificity of the TFIIIB-TATA box DNA complex. The apparent dissociation constant for this protein-DNA interaction is approximately 0.4 nM, similar to the affinity of yeast TBP for the same sequence. TFIIIB transcriptional activity and TATA-box binding activity cofractionate during a series of four ion-exchange chromatographic steps, and reconstituted transcription reactions demonstrate that the TATA-box DNA-protein complex contains TFIIIB TAF activity. Polypeptides with apparent molecular masses of 75 and 92 kDa are associated with TBP in this complex. These polypeptides were renatured after elution from sodium dodecyl sulfate-gels and tested individually and in combination for TFIIIB TAF activity. Recombinant TBP along with protein fractions containing the 75- and 92-kDa polypeptides were sufficient to reconstitute TFIIIB transcriptional activity and DNA binding activity, suggesting that Xenopus TFIIIB is composed of TBP along with these polypeptides.